Republic of North Macedonia : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of North Macedonia. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2020)
This 2019 Article IV Consultation with Republic of Macedonia discusses that after a protracted political crisis, the economy has entered a period of solid growth and stability. Over the recent years, the authorities have reviewed the reform momentum, with crucial institutional and governance reforms and efforts to make public finances more sustainable and equitable. Growth is expected to accelerate in 2020. Lower taxes and higher pensions and wages?including public sector and minimum wages?are expected to provide a further, albeit one-off, stimulus to consumption. Export and investment growth would remain robust but slow somewhat, reflecting weak growth in trading partners. An ambitious consolidation is needed to rebuild fiscal policy space and re-orient public spending toward investment. Reforms to address key labor market and institutional weaknesses will help lift medium-term growth and speed up income convergence. Although growth has been solid in the past two decades, it has not been enough to substantially narrow North Macedonia's large income gap with the European Union. In order to accelerate convergence, it is essential to continue reforms to improve the public administration, rule of law, and control of corruption.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet